Insight into the soil seedbank characteristics of the arid rangelands in Libya: A case study in Marmarica Plateau, Cyrenaica (Northeastern part of Libya) - Saaed, Manam; El-Barasi, Yacoub; Elhashani, Nazeeha (Libyan Journal of Science &Technology, 2022)
The current study was conducted in Daphna area, an arid region in Cyrenaica located at the northeastern part of Libyan Sea Coast at the Libyan-Egyptian Border. The soil was sampled in 40 different sampling sites along five different sectors through scraping the soil from 0-10 cm layer (25´25 cm) in the Platea and from 0-10 cm and 10-30 cm layers in the depressions and valleys. Using the floatation in a salt solution method, the seeds were extracted from the soil, counted and identified. The majority of the extracted seed were tinny (< 5 mm) and mainly belonged to annual species. Seeds density in the plateau ranged between 0 and 25400 seed m-2 with an overall mean of 4110 seed m-2 (±949.30 SE), which is adequate density when compared to similar arid ecosystems. The low-lying lands in depressions (Sakifas) and valleys (Wadis) retained higher seed density than the higher-lying lands on the plateau, and the northern areas retained higher density than the southern areas. The higher top soil layer (0-10 cm) in both Sakifas and behind the Dykes in valleys retained higher mean density than the layer (10-30 cm). The homogeneity of seed characteristics across the plateau and the dominance of annual and short-lived species could be a sign of degradation, and the absence of many perennial species in the soil seedbank may hamper any conservation or rehabilitation effort to improve these rangelands.